Mining Stack Overflow for discovering error patterns in SQL queries - Nagy, Csaba; Cleve, Anthony (ICSME : 2015 IEEE International Conference on Software Maintenance and Evolution : September 29, 2015-October 1, 2015, 2015)
Constructing complex queries in SQL sometimes necessitates the use of language constructs and the invocation of internal functions which inexperienced developers find hard to comprehend or which are unknown to them. In the worst case, bad usage of these constructs might lead to errors, to ineffective queries, or hamper developers in their tasks. This paper presents a mining technique for Stack Overflow to identify error-prone patterns in SQL queries. Identifying such patterns can help developers to avoid the use of error-prone constructs, or if they have to use such constructs, the Stack Overflow posts can help them to properly utilize the language. Hence, our purpose is to provide the initial steps towards a recommendation system that supports developers in constructing SQL queries. Our current implementation supports the MySQL dialect, and Stack Overflow has over 300,000 questions tagged with the MySQL flag in its database. It provides a huge knowledge base where developers can ask questions about real problems. Our initial results indicate that our technique is indeed able to identify patterns among them.